Enlightened nation building : the "science of the legislator" in Adam Smith and Rousseau - Hanley, Ryan Patrick (2008)
Contiene bibliografía
Keywords: Rousseau, Jean-Jacques -- (1712-1778); Nacionalismo; Smith, Adam -- 1723-1790